(untitled) (The Macau Ricci Institute Journal, 2023)
In the 18th century, the world was fraught with wars and religious conflicts. The Catholic Church and Protestantism were at bitter odds, and only business was the most secure field. Voltaire said: Take a view of the Royal Exchange in London, a place more venerable than many courts of justice, where the representatives of all nations meet for the benefit of mankind. There the Jew, the Mahometan, and the Christian transact together, as though they all professed the same religion, and give the name of infidel to none but bankrupts. There the Presbyterian confides in the Anabaptist, and the Churchman depends on the Quaker’s word. At the breaking up of this pacific and free assembly, some withdraw to the synagogue, and others to take a glass. This man goes and is baptized in a great tub, in the name of the Father, Son, and Holy Ghost: that man has his son’s foreskin cut off, whilst a set of Hebrew words (quite unintelligible to him) are mumbled over his child. Others retire to their churches, and there wait for the inspiration of heaven with their hats on, and all are satisfied. (Voltaire, c.1778) Voltaire painted a picture of commercial justice. In an era of political and religious conflicts, commerce provides an arena of harmony and mutual exchanges. Commerce was the highest goodness in the world then. Self-interest was acknowledged by all religions and peoples. In commerce, everybody treats one another equally in harmony without ideological conflicts.